2015
DOI: 10.1016/j.medici.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood Th9 cells and eosinophil apoptosis in asthma patients

Abstract: Patients with allergic asthma demonstrate increased peripheral blood Th9 cells count and serum IL-9, while eosinophil apoptosis is inversely related to IL-9 concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 28 publications
2
25
0
5
Order By: Relevance
“…Consistent with a previous finding that constitutive overexpression of IL‐9 in lung reproduces a part of pathological features of asthma, several murine studies have indicated that Th9 cells play substantial roles in the pathogenesis of asthma . In addition, a recent clinical study has shown that the number of Th9 cells is increased in the peripheral blood in patients with asthma as compared with that in control subjects . These results suggest that Th9 cells also play a role in the pathogenesis of asthma.…”
Section: Roles Of Other Helper T‐cell Subsets In Asthmasupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with a previous finding that constitutive overexpression of IL‐9 in lung reproduces a part of pathological features of asthma, several murine studies have indicated that Th9 cells play substantial roles in the pathogenesis of asthma . In addition, a recent clinical study has shown that the number of Th9 cells is increased in the peripheral blood in patients with asthma as compared with that in control subjects . These results suggest that Th9 cells also play a role in the pathogenesis of asthma.…”
Section: Roles Of Other Helper T‐cell Subsets In Asthmasupporting
confidence: 86%
“…[83][84][85][86] In addition, a recent clinical study has shown that the number of Th9 cells is increased in the peripheral blood in patients with asthma as compared with that in control subjects. 87 These results suggest that Th9 cells also play a role in the pathogenesis of asthma.…”
Section: Th9 Cells In Allergic Airway Inflammationmentioning
confidence: 89%
“…In previous study, allergic patients had elevated Th9 cells in peripheral blood mononuclear cells together with elevated serum IgE levels 35. A recent study showed that serum IL-9 concentrations in patients with allergic asthma were increased and inversely related to eosinophil apoptosis 36. Another study reported that IL-9 gene expression in serum samples was increased in asthmatics, which was correlated with disease severity 37.…”
Section: Discussionmentioning
confidence: 96%
“…The Th22 frequency is currently considered as a biomarker for disease progression in several diseases (89)(90)(91)(92). This finding illustrates that not only Th2 cells are important for allergy, rhinitis and asthma, but also other subsets such as Th9 cells (93), which remain to be further characterized.…”
Section: T-cell-associated Biomarkersmentioning
confidence: 87%